The influence of fanaticism and financial literacy on consumptive behavior with self-control as a moderating variable: a study on K-pop fans in Salatiga - Auliya Itsna Hanifah; Faqiatul Mariya Waharini (Prodi Magister Ekonomi Syariah FEBI UIN Walisongo Semarang, 2025)
This study investigates the influence of fanaticism and financial literacy on consumptive behavior among K-pop fans in Salatiga, with self-control as a moderating variable. The research was motivated by the growing phenomenon of excessive consumption driven by fandom culture, particularly among youth influenced by K-pop idols. The purpose of the study is to analyze how emotional attachment (fanaticism) and financial awareness (financial literacy) shape individual spending patterns, and to determine whether self-control can mitigate impulsive consumption tendencies. A quantitative approach was applied, involving 100 respondents selected through purposive sampling. Data were collected using structured questionnaires and analyzed with SPSS version 25 through classical assumption tests, t-tests, and Moderated Regression Analysis (MRA). The findings reveal that fanaticism significantly and positively affects consumptive behavior, while financial literacy has a significant negative effect. Furthermore, self-control moderates the relationship between fanaticism and consumptive behavior, indicating that higher self-control can reduce the influence of fanaticism on impulsive spending. However, self-control does not moderate the effect of financial literacy, suggesting that financially literate individuals already exercise sufficient self-regulation in managing expenses. These results highlight the complex interaction between emotional and cognitive factors in shaping consumer behavior. The study contributes to Islamic behavioral economics by emphasizing the importance of moderation and self-control as ethical principles guiding financial responsibility. It also provides practical implications for educators and policymakers in promoting financial literacy and emotional awareness among young consumers.